1997
DOI: 10.1016/s0169-5150(97)00024-8
|View full text |Cite
|
Sign up to set email alerts
|

Technical efficiency in the Spanish agrofood industry

Abstract: This study estimates frontier production functions with cross-section data for the Spanish agrofood industry by using deterministic and stOC~astie parametric approaches. We compute the individual technicul efficiency for each finn. compare the results and cxplain thẽ elatlOnship between technical efficiency and other relevant quantitatj~e varia~les. The results indicate that the Spanish agrofood industry as a levet of effieiency between 68% and 93%; which means that n IS potentially capable of increasing produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Ambali (2012) found that food crop farmers in Nigeria had a mean technical e ciency with room for improvement in allocative and economic e ciency. Apezteguía(1997) similarly found a range of 68-93% e ciency in the Spanish agrifood industry, positively correlated with factor productivity and labor costs. Karagiannis and Sarris (2005) Singh, 2019), irrigation infrastructure (Singh, 2019;Wadud, 2003), agricultural machinery (Ren & Li 2020) and pesticides (Masuda, 2018).…”
Section: Agricultural Production E Ciencymentioning
confidence: 80%
“…Ambali (2012) found that food crop farmers in Nigeria had a mean technical e ciency with room for improvement in allocative and economic e ciency. Apezteguía(1997) similarly found a range of 68-93% e ciency in the Spanish agrifood industry, positively correlated with factor productivity and labor costs. Karagiannis and Sarris (2005) Singh, 2019), irrigation infrastructure (Singh, 2019;Wadud, 2003), agricultural machinery (Ren & Li 2020) and pesticides (Masuda, 2018).…”
Section: Agricultural Production E Ciencymentioning
confidence: 80%
“…Over the years, a series of methods has been developed to determine the technical efficiency of production units (Apezteguia and Garate, 1997). More so, measuring efficiency is important in the use of scarce resources in production.…”
Section: Problem Statementmentioning
confidence: 99%
“…It indicates that the outer bound output frontier varies from farm to farm and for the same farm over time (Kalirajan and Shand, 1994). It represents the statistical noise outside the control of the farmer (Apezteguia and Garate, 1997).…”
Section: Omitted Variables In the Analysismentioning
confidence: 99%
“…For example, Tarıkahya (1991) compared productivity and technical features among flour factories, Bingöl (1992) examined input use and productivity problems of the vegetable processing industry in the Aegean and Marmara regions and later revealed (Bingöl, 1993) input problems and partial and total factor productivity in the fruit processing industry, Demirci (2001) analyzed performances and total factor productivity in sugar factories. Several studies have also addressed efficiency and (or) competitiveness in the agro-food sector of different countries (Apezteguía and Garáte, 1997;Doucouliagos and Hone, 2000;Oustapasidis et al, 2000;Margono and Sharma, 2006;Sena, 2006;Pérez et al, 2007;Van der Vlist et al, 2007;Latruffe, 2010;Putićová and Mezera, 2011;Reddy and Bantilan, 2012;Furesi et al, 2013). However, no previous studies have examined firmlevel economic efficiency and its determinants within Turkey's agro-food industry.…”
Section: Introductionmentioning
confidence: 99%